A carismática constituição de uma autoridade racional: um estudo sobre a Comunidade Católica Shalom - Silva, Emanuel Freitas da (2019)
This research aims at understanding the rational-bureaucratic construction of leaders believed to be "charismatic" within charismatic Catholicism and who maintain their authority over time through institutional mechanisms. For this, the person of Moyses de Azevedo, founder and general moderator of the Shalom Catholic Community, who, from its centrality, exercises a considerable domination over this collectivity is taken as the case. Founded in the city of Fortaleza in 1982, the Shalom Catholic Community, now present in more than 30 countries, is one of the major forces in the construction of a cafeteria that serves as an "evangelization" channel. within the contemporary charismatic Catholicism, appearing as the most important of the "New Communities" Catholic of Brazilian origin, and one of the most important in the level of global Catholicism. The centrality in the figure of its founder, Moysés Azevedo, a charismatic person of whom in the belief of the community body emanates the "vocation" and "Shalom charism", underpin the central problem of this thesis: that corporate processes, within the Community, produced the exceptionality of its founder, Moyses Azevedo, and how such processes were accompanied by the production of a subalternized, or "less exceptional" place for other internal leaderships? Knowledge of the historical formation of the Community, reading of its documents and internal training materials, participant observation in various community events, interviews with members, former members and Catholic authorities, as well as a thorough bibliographical review of the sociological problematic of the "charism" served as methodological contributions that guided this research. In the end, we will see the important role played by bureaucratic and rational mechanisms to produce, legitimize and reproduce mechanisms of domination believed to be "charismatic", punctuating the intrinsic relationship between charism and rational-bureaucratic structures.